Anti-Bacterial Role of Asparagus Racemosus: A Review (International Journal of Innovative Research in Engineering & Management, 2021)
The antimicrobial peptides (AMPs) are integral portion of the  human’s innate immune system showing broad-spectrum  antimicrobial roles. AMPs are used for antimicrobial therapy  due to the increase in the cases of resistance towards  conventional antibiotics. Unfortunately, resistance towards  AMPs and their derivatives are also showing an increase. In this  paper, the flowers of the vegetable Asparagus racemosus were  evaluated for its anti-microbial activity on two species of the  genus lactobacillus, Lactobacillus acetotolerans &  Lactobacillus acidifarinae. Firstly, various extracts of  Aqueous, methanol, ethanol, butanol were made. The AMP,  Cecropine A was chosen as positive control & the Dimethyl  sulfoxide (DMSO) was chosen as the negative control. Then  the paper discs were soaked in these extracts and were kept on  the lawn culture. After 24 hours, the ethanolic extract showed  the highest inhibition whereas DMSO showed the least activity.  These results open up possibility that this common vegetable  can be utilized for the commercial production of anti-microbial  agents.
Keywords: Antimicrobial peptides; Asparagus racemosus; Antimicrobial resistance; Cecropine A; extracts; paper disks; zone of inhibition